Information Asymmetries in Developing Country Financing - Anayotos, George (IMF Working Papers; Working Paper, 1994)
This paper assesses the impact of information asymmetries on developing country financing and considers alternative techniques to reduce the adverse implications of such asymmetries. Following an introduction, Section II examines in general terms the role of information in financial markets and analyzes the incentive and risk sharing properties of alternative financial contracts. Information asymmetries which are present in domestic finance are more prevalent in international finance, in particular in developing country financing. Section III reviews measures aiming to resolve information asymmetries. Borrowing and creditor country regulations and policies, as well as innovative contractual agreements help to resolve a range of issues related to information asymmetries. However, despite their contribution, residual problems remain unresolved. The international financial institutions, and in particular the Fund, have an important role to play in alleviating information asymmetries.